The Effect of Problem-Based Learning Model on Physical Education Learning in Volleyball Games at Smk Candra Naya Jakarta - Saipul Rohman (International Journal of Education and Literature, 2025)
This study aims to examine the effect of the Problem Based Learning (PBL) model in Physical Education learning for volleyball at SMK Candra Naya Jakarta. The research method used was an experiment with a One Group Pretest-Posttest design. The sample consisted of 39 eleventh-grade students selected using Cluster Random Sampling technique. The research instrument was a test of overhead and underhand passing skills in volleyball. The results showed that the average pretest score of 14.05 increased to 17.77 in the posttest, with hypothesis testing (Paired Samples Test) yielding tcount > ttable (9.833) and a significance of 0.000 (p < 0.05). This proves that the PBL model significantly improves students’ volleyball passing skills. Additionally, PBL encourages active participation, teamwork, and critical thinking skills. Therefore, the PBL model can be an innovative alternative in Physical Education learning, particularly for volleyball.